HUBUNGAN GAYA HIDUP DAN TINGKAT KECEMASAN DENGAN HIPERTENSI PADA LANSIA - Wahyu, Wahyu Arif Mahfudin; Permatasari, Indah (JURNAL SMART ANKes, 2025)
Every elderly person must have a different lifestyle and anxiety level in dealing with hypertension. Lifestyle can be influenced by physical activity, diet, rest, smoking, as well as the level of anxiety in the elderly. This study aims to determine the relationship between lifestyle and anxiety levels in the elderly with hypertension in the Petaling Health Center area in 2025. This research method is a quantitative study with a cross-sectional approach. The population in this study were elderly people aged 45-90 years who had hypertension in the Petaling Health Center area in 2025. The data collection method used questionnaires and questionnaires using interviews. The results of this study found that there was a correlation between lifestyle in the elderly with hypertension in the Petaling Health Center with a p value = 0.000 < (0.005) so it was concluded that H0 was rejected and the results of this study also found that there was a correlation between lifestyle and the correlation of anxiety levels in the elderly with hypertension in the Petaling Health Center with a p value = 0.005 < (0.005) so it can be concluded that H0 was rejected. This study recommends that students, particularly final-year students, learn from this study to understand the relationship between lifestyle and anxiety levels in the elderly and hypertension in the Petaling Community Health Center (Puskesmas) in 2025. Keywords: Lifestyle, Hypertension, Elderly, and Anxiety Levels.